Analisis Praktik Wacana Mengenai Kelompok LGBT dalam Publikasi Daring Feminis - Anggita Ayu Indari; Wiwik Novianti (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
Nowadays, the discourse of LGBT people in Indonesia’s mainstream media is still so heteronormative and religious-bias. Contrarily to the fact, there is still a media that offers an alternative even though most of Indonesian Media only covers prominent discourse regarding to LGBT people. Magdalene is the example of one of them. Through their online publication, Magdalene tries to challenge the hegemony of mainstream media which often marginalizes, subordinates, and stigmatizes LGBT people. It is quite interesting because actually Magdalene is created as feminist publication which covers the voice of women, not particularly LGBT people. This study aims to find out how the contents about LGBT people in Magdalene’s online publication is influenced by the discourse practice of the media. In conducting the analysis, researcher uses the Discourse Practice Analysis based on Norman Fairclough’s Critical Discourse Analysis. Additionally, the analysis is also based on Reese & Shoemaker’s Hierarchy of Influences on Media Content. In the end, the result shows that the discourse of LGBT people in Magdalene’s online publication is significantly influenced by personal attitudes, beliefs, and values upheld by the editorial team.